IMPLEMENTASI PEMBINAAN DANA BANTUAN OPERASIONAL SATUAN PENDIDIKAN JENJANG SEKOLAH MENENGAH PERTAMA DI KOTA JAMBI - Erwan Nur Arief; Siti Zubaidah; Rian Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the School Operational Assistance Fund (BOSP) guidance program at the junior secondary school level in Jambi City. The study employed a qualitative approach with a descriptive method. The research informants consisted of the Head of the Junior Secondary Education Division of the Jambi City Education Office, the BOSP Management Team of the Jambi City Education Office, and principals from one public and one private junior secondary school selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing/verification. Data trustworthiness was ensured through credibility, transferability, dependability, and confirmability. The findings indicate that the implementation of the BOSP guidance program in Jambi City has been carried out effectively based on the indicators of program understanding, target accuracy, timeliness, goal attainment, and tangible outcomes. Guidance activities, including socialization, technical assistance, coaching clinics, and support in the use of the ARKAS application, have enhanced schools' understanding and compliance with BOSP management, resulting in more orderly, transparent, and accountable financial governance. However, several challenges remain, including frequent regulatory changes, disparities in the competencies of BOSP management personnel, and delays in fund disbursement. In addition, the evaluation of the guidance program has primarily focused on administrative compliance and has not comprehensively assessed its impact on educational quality improvement. Therefore, future guidance programs should emphasize strengthening the competencies of BOSP managers, improving performance-based monitoring and evaluation systems, and developing success indicators that are oriented toward enhancing the quality of education.